3D-QSAR analysis of the interactions of flavonoids with human organic cation transporter 2. (1st September 2022) - Bi, Yajuan; Wang, Xue; Li, Huixiang; Tian, Yiqing; Han, Lifeng; Gui, Chunshan; Zhang, Youcai
Abstract: Flavonoids are a class of phenolic and polyphenolic compounds widely distributed in vegetables, fruits, grains and herbs. Organic cation transporter 2 (OCT2) mediates the renal secretion of organic cations and is a key site of drug-drug interactions (DDIs). In this study, we systematically investigated the inhibitory effect of 28 flavonoids on OCT2-mediated uptake of 4–4-dimethylaminostyryl-N-methylpyridinium (ASP + ). Among them, scullcapflavone II demonstrated the strongest inhibitory effect on OCT2-mediated uptake of ASP + (IC50 =11.2 μM) in a competitive manner. Next, 3D-QSAR analyses of flavonoid OCT2 inhibitors were performed using both CoMFA and CoMSIA models. The date revealed that bulky substituents at the C-3 and C-4 positions of ring C as well as the C-7 position of ring A could prevent the interactions of flavonoids with OCT2. In contrast, a hydrophilic and negatively charge substituent on ring A was favorable for the interactions of flavonoids with OCT2. Consequently, baicalin (IC50 =220.2 μM) with a uronic acid substituent on ring A exhibited a stronger inhibition than baicalein (IC50 =294.5 μM); quercetin-3-O-galactoside (IC50 =497.4 μM) was a stronger inhibitor of OCT2 than rhamnetin 3-galactoside (IC50 =1409.0 μM). Taken together, our findings could be valuable in elucidating and predicting the interactions of flavonoids with OCT2. Graphical Abstract: ga1 Highlights: Inhibitory effects of 28 flavonoids on OCT2 were investigated. CoMFA and CoMSIA models were developed for flavonoids as OCT2 inhibitors. Bulky substituents at C-3, C-4 positions of ring C or C-7 position of ring A were important. Hydrophilicity of ring A contributes to the interactions of flavonoids with OCT2.